Clinical impact of obsessive-compulsive disorder comorbidity in bipolar disorder: a systematic review and meta-analysis : OCD in BD: a review on clinical impact : review/meta-analysis - De Prisco, Michele; Tapoi, Cristiana; Oliva, Vincenzo; Strumila, Robertas; Takami, Christine; Girone, Nicolaja; Macellaro, Monica; Andrade, Juliana Braga de Salles; Schmitz, Christian N.; Vieta, Eduard; Fico, Giovanna (European psychiatry, 2025)
BackgroundBipolar disorder (BD) is commonly comorbid with other psychiatric conditions, such as obsessive-compulsive disorder (OCD). Despite increasing interest in this comorbidity, quantitative data on its clinical characteristics remain limited. This systematic review and meta-analysis aimed to evaluate the clinical impact of OCD comorbidity in BD by comparing individuals with BD and OCD (BD-OCD) to those with BD without OCD.MethodsWe systematically searched the PubMed/MEDLINE, Scopus, PsycINFO, and Web of Science databases up to April 15, 2024. Meta-analyses were conducted to compare BD-OCD and BD without OCD groups across multiple clinical domains.ResultsFrom 11,959 initial records screened, 26 studies were included in the qualitative synthesis, with 22 eligible for meta-analysis. Individuals with BD-OCD showed higher odds of experiencing chronic mood episodes (OR = 9.42; 95%CI = 2.23, 39.9), rapid cycling (OR = 1.92; 95%CI = 1.04, 3.53), comorbid eating disorders (OR = 3.37; 95%CI = 1.99, 5.7), panic disorder (OR = 3.3; 95%CI = 2.11, 5.2), substance use disorders (OR = 1.39; 95%CI = 1.02, 1.89), and lifetime suicide attempts (OR = 1.85; 95%CI = 1.21, 2.84). Additionally, they presented earlier onset of BD (SMD = -0.27; 95%CI = -0.52, −0.01) and reduced functioning (SMD = -0.42; 95%CI = -0.59, −0.24). Most data were derived from adult populations, limiting the evidence available for children and adolescents.ConclusionsBD-OCD presents a more severe and complex clinical profile, requiring specialized assessment and integrated treatment approaches. Identifying these features may support earlier recognition and inform personalized interventions for this population.
Gesehen am 15.01.2026